Pre-service EFL teachers’ anxiety during teaching practicum - Adinda, Tiara; Jaufillaili; Apandi (Research and Innovation in Language Learning, 2025)
Teaching practicum is important stage for all students in university, because it allows them to put into practice what they have learned in university courses and allows them to interact directly with students in school. However, Anxiety is one of the critical issues that EFL pre- service teachers face when doing classroom teaching during a practicum program. This study aimed to know what factors can provoke anxiety of pre-service teachers in the English Education Department at a private university in Cirebon during teaching practicum and to know what strategies are used by pre-service teachers to overcome with their anxieties. In this study, qualitative research with a case study approach was used to answer the research questions, and data were collected through interviews. Based on the data obtained from the interviews, the researcher discovered several factors that can provoke anxiety in pre-service teachers during teaching practicum. There is a lack of teaching experience, being observed by teacher, classroom management, proficiency in English, and unfamiliarity with the Environment. While the strategies used by pre-service teachers to overcome their anxieties during teaching practicum are preparation, increasing self-confidence, and relaxation. The findings of this study provide information for university supervisors, mentors, and student teachers.